Enhanced Data Security of Communication System Using Combined Encryption and Steganography - Alrikabi, Haider Th.Salim; Tuama Hazim, Hussein (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Data security has become a paramount necessity and more obligation in daily life. Most of our systems can be hacked, and it causes very high risks to our confidential files inside the systems. Therefore, for various security reasons, we use various methods to save as much as possible on this data, regardless of its different forms, texts, pictures, videos, etc. In this paper, we mainly rely on storing the basic image which should be protected in another image after changing its formal to composites using the DWT wavelet transform. The process of zeroing sites and storing their contents technique is used to carry the components of the main image. Then process them mathematically by using the exponential function. The result of this process is to obtain a fully encrypted image. The image required to be protected from detection and discrimination is hidden behind the encrypted image. The proposed system contains two algorithms. the first algorithm is used for encryption and hiding, but the second algorithm is designed for returning and decoding the main image to its original state with very efficiently.